Assessment of Students’ Writing Acquisition - Wayan Maba (International Journal of Social Science, 2022)
Writing is one of the essential language skills to be mastered by students to communicate appropriately in written forms. Nowadays, writing is becoming a vital skill for modern communication as an increasing number of people communicate in written forms using various communication technology. This study was conducted to analyse students’ writing abilities. An ex post facto research design was conducted to collect the data required for this study. A writing assessment was administered to the selected samples, and the data were analysed descriptively. This study found that students writing skills was at a sufficient level. It means several students are still experiencing difficulty in writing. Therefore, this study implied that students’ writing skills should continually develop to a higher level of acquisition